An exploratory study on the lived experiences of hoarding in Singapore. (4th November 2019) - Subramaniam, Mythily; Jeyagurunathan, Anitha; Devi, Fiona; Chang, Shi Hui Sherilyn; Samari, Ellaisha; Verma, Swapna Kamal; Ng, Wei Lik Jared; Tan, Weng Mooi; Chong, Rebecca; Ye, Peishan; Lim, Lea Lea; Babjee, Ramzi; et al.
Abstract: Research studies have revealed that people with hoarding typically collect and keep items due to their aesthetic appeal, utility and strong emotional attachment to the items resulting in clutter and limiting living spaces. This study aims to explore the experiences of individuals with hoarding disorder to understand and describe—the patterns and reasons for hoarding, experiences with decluttering and the impact of hoarding disorder on significant others and society in the context of a multi‐ethnic urban Asian country. A total of 12 participants with hoarding disorder were recruited and interviewed using a simple semi‐structured interview guide designed for the study. The resulting transcribed interviews were analysed using thematic analysis. The mean age of the participants was 56.7 years ( SD  = 14.5). Nine super‐ordinate and discrete but interconnecting themes emerged from the qualitative interviews: types of hoarded items, sources of hoarded items, ways of storing/arranging hoarded items, help‐seeking/treatment contact, reasons for hoarding, experiences with decluttering, impact upon family, community and self, restricting hoarding behaviours and insight. Key themes identified in the study are consistent with the literature on studies on hoarding which have been done in other populations. Hoarding in the community has serious consequences for individuals with hoarding disorder and others living in the community, which is compounded by the lack of insight among these individuals. There is a pressing need to increase public awareness and recognition of hoarding behaviours to aid efforts in bringing timely and appropriate services to the affected individuals.